The role of preconditioning on landfast sea ice break-off processes in Admiralty Inlet, Nunavut - Ada Loewen; Gregory Crocker; Derek Mueller; Richard McKenna (Arctic Science)
Due to changes in the Arctic climate, the timing of spring break-up of landfast sea ice has become less predictable in recent years, which has implications for the traditional lifestyle of Inuit and shipping operations. We use satellite imagery from multiple sources to identify the timing of major spring sea ice break-off events in Admiralty Inlet, Nunavut from 2000 to 2022. The factors leading up to a major break-off event in 2022 are examined more closely using in situ and re-analysis of meteorological and oceanographic data and numerical experiments using a finite element model (FEM). The model enabled us to explore the effects of environmental stresses, aajurait (open leads), and shore leads on sea ice deformation prior to break-off. The development of our modelling approach and interpretation of results was informed by Inuit Knowledge. Modelled stress magnitudes are typically too small for widespread new fractures to occur under typical spring ice conditions. Rather, observations and FEM output suggest that the development of leads precondition the ice to allow relatively low wind and current forces to initiate break-off events.